2008
DOI: 10.1097/mpg.0b013e318145a70c
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Intolerance and Gastrointestinal Motility in Adolescents With Nausea and Abdominal Pain

Abstract: Although altered gastric emptying and postural tachycardia are common in a referral population of adolescents with nausea and/or abdominal discomfort, the clinical presentation was not predictive of test results. Furthermore, delayed gastric emptying was not correlated with the current definition of postural tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 22 publications
7
41
0
Order By: Relevance
“…In a subsequent study that used electrogastrography to assess changes in the fundus and antral regions of the stomach, electrical activity was normal in the supine position, but became abnormal in the upright position. (13) These measurements suggested that electrical activity increased in the fundal region (tachygastria) and slowed in the antrum (bradygastria).Previous studies have shown that gastric emptying time correlated poorly with symptoms of OI and heart rate response to TTT (8,. 11) Our data confirms the poor reliability of GES and its correlation with abnormal motility.…”
supporting
confidence: 90%
“…In a subsequent study that used electrogastrography to assess changes in the fundus and antral regions of the stomach, electrical activity was normal in the supine position, but became abnormal in the upright position. (13) These measurements suggested that electrical activity increased in the fundal region (tachygastria) and slowed in the antrum (bradygastria).Previous studies have shown that gastric emptying time correlated poorly with symptoms of OI and heart rate response to TTT (8,. 11) Our data confirms the poor reliability of GES and its correlation with abnormal motility.…”
supporting
confidence: 90%
“…Abdominal pain and recurrent nausea are common among children with POTS and it is known to co-exist with FGIDs. 25,26 We cannot rule out the possibility that some children may have had POTS and not FAP complicated by nausea. We also did not perform gastric emptying studies in all participants to rule out gastroparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Patterning of linked to OI hemodynamic responses may enhance qualitative VM evaluation and thus improve the diagnosis of various autonomic disorders characterized by orthostasis. Improved VM assessment would be clinically beneficial, as OI can be a substantial cause of morbidity (2,11,21,23,27). Therefore, the present study's aim was to clarify the contribution of the VM to the diagnosis of OI.…”
mentioning
confidence: 98%